One-Pot Synthesis of Quinolin-4(1H)-one Derivatives by a Sequential Michael Addition–Elimination/Palladium-Catalyzed Buchwald–Hartwig Amination Reaction - Wang, Yinghua; Liang, Hanyu; Chen, Chunxia; Wang, Deqiang; Peng, Jinsong (Synthesis, 2015)
A convenient approach has been developed for the construction of quinolin-4(1H)-one frameworks, starting from (Z)-β-chlorovinyl aromatic ketones and amines. Intermolecular Michael addition of an amine to a (Z)-β-chlorovinyl ketone was followed by elimination of a chloride anion to give enamine intermediates, with full retention of the initial Z-configuration. The enamine intermediates were transformed into quinolin-4(1H)-one products by a palladium-catalyzed intramolecular N-arylation in a tandem one-pot manner, with good to excellent yields.
Keywords: quinolines; ketones; Michael additions; aminations; tandem reactions; cyclizations